European multi-centre study of the Nucleus Hybrid L24 cochlear implant. (December 2013) - Lenarz, Thomas; James, Chris; Cuda, Domenico; Fitzgerald O'Connor, Alec; Frachet, Bruno; Frijns, Johan H.M.; Klenzner, Thomas; Laszig, Roland; Manrique, Manuel; Marx, Mathieu; Merkus, Paul; Mylanus, Emmanuel A.M.; et al.
Abstract Objectives: To investigate the preservation of residual hearing in subjects who received the Nucleus Hybrid L24 cochlear implant. To investigate the performance benefits up to one year post-implantation in terms of speech recognition, sound quality, and quality of life. Design: Prospective, with sequential enrolment and within-subject comparisons. Post-operative performance using a Freedom Hybrid sound processor was compared with that of pre-operative hearing aids. Study sample: Sixty-six adult hearing-impaired subjects with bilateral severe-to-profound high frequency hearing loss. Results: Group median increase in air-conduction thresholds in the implanted ear for test frequencies 125–1000 Hz was < 15 dB across the population; both immediately and one year post-operatively. Eighty-eight percent of subjects used the Hybrid processor at one year post-op. Sixty-five percent of subjects had significant gain in speech recognition in quiet, and 73% in noise (≥ 20 percentage points/2 dB SNR). Mean SSQ subscale scores were significantly improved (+ 1.2, + 1.3, + 1.8 points, p < 0.001), as was mean HUI3 score (+ 0.117, p < 0.01). Combining residual hearing with CI gave 22−26 %age points mean benefit in speech recognition scores over CI alone (p < 0.01). Conclusions: Useful residual hearing was conserved in 88% of subjects. Speech perception was significantly improved over preoperative hearing aids, as was sound quality and quality of life.